High-thermal-conductivity pressure-resistant ceramic aluminum substrate and preparation method thereof
Patent Information
- Application Number
- CN202611277874.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-09-25
AI Technical Summary
[0007]本发明的目的在于提供一种高导热耐压陶瓷铝基板及其制备方法,以改善多孔陶瓷化氧化铝过渡层孔道残余空隙、铝基层与高分子绝缘层界面结合稳定性不足,以及导热填料体系在高耐压场景下绝缘稳定性不足的技术问题
1、本发明的多孔陶瓷化氧化铝过渡层提供具有孔道的陶瓷化界面,反应型高分子封孔层经真空浸润后能够形成孔内填充部,减少孔道残余空隙和界面薄弱点,从而有利于提高击穿稳定性和湿热后绝缘保持能力。反应型高分子封孔层还包括覆盖在陶瓷化氧化铝过渡层表面的表面连接部,该表面连接部与孔内填充部连续设置,使陶瓷化层与高导热耐压高分子绝缘层之间形成由孔内到表面的连续过渡界面,从而有利于提高铜箔剥离强度和冷热冲击后的层间稳定性。
Smart Images

Figure CN122808287A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal-based copper clad laminate technology, specifically to a high thermal conductivity and pressure-resistant ceramic aluminum substrate and its preparation method. Background Technology
[0002] Aluminum-based copper clad laminates typically consist of an aluminum substrate, an insulating and thermally conductive layer, and a copper foil layer. The aluminum substrate provides mechanical support and heat dissipation channels, the copper foil layer forms the circuitry, and the insulating and thermally conductive layer simultaneously serves as a thermal conductor, an electrical insulation layer, and an interlayer bonding layer between the aluminum substrate and the copper foil layer. With the increasing operating voltage and power density of power electronic devices, the insulating and thermally conductive layer of aluminum-based copper clad laminates not only needs to have low thermal resistance but also needs to ensure withstand voltage stability, peel strength, solder heat resistance, damp heat reliability, and thermal shock reliability.
[0003] Existing technologies disclose a process of ceramicizing an aluminum plate surface, forming a surface treatment layer on the ceramic surface of the ceramic aluminum plate, coating the ceramic surface of the surface-treated ceramic aluminum plate with a high thermal conductivity adhesive layer, and then stacking the ceramic aluminum plate coated with the high thermal conductivity layer with copper foil and performing vacuum hot pressing. This method can improve the thermal conductivity and insulation properties of aluminum-based copper-clad laminates with the combination of ceramic aluminum plate and high thermal conductivity adhesive layer. However, its surface treatment layer is mainly used to improve the bonding between the ceramic surface and the adhesive layer, and does not provide a reactive polymer sealing layer for the porous ceramicized alumina layer to form an internal filling part and a surface connection part.
[0004] Existing technologies disclose high thermal conductivity and high voltage resistance aluminum-based copper clad laminates composed of copper foil, an insulating and thermally conductive adhesive layer, an adhesive layer, and an aluminum plate. The aluminum plate surface undergoes anodizing to form a ceramic protective layer, and the insulating and thermally conductive adhesive layer can be formulated from epoxy resin, toughening agent, coupling agent, curing agent, and thermally conductive filler. This approach improves the performance of the aluminum-based copper clad laminate through the anodized ceramic protective layer, adhesive layer, and insulating and thermally conductive adhesive layer. However, the relationship between the ceramic protective layer and the insulating and thermally conductive adhesive layer still primarily relies on ordinary adhesive layers or conventional coupling agent systems, failing to form a reactive polymer sealing interface containing multiple functional groups.
[0005] Existing technologies disclose solutions involving an aluminum substrate layer, a thermally conductive insulating layer, and a copper foil layer. The thermally conductive insulating layer uses boron nitride-modified nitrogen-doped graphene as the thermally conductive filler. This solution improves the thermal conductivity of the insulating layer by modifying the thermally conductive filler. However, graphene-based fillers inherently possess conductive or semi-conductive properties. For long-term high-voltage applications, volume resistivity, dielectric loss, and local breakdown stability still require attention.
[0006] Therefore, for ceramic aluminum substrates for power electronics, it is still necessary to provide a new interlayer interface structure and preparation method to effectively utilize and seal the pores of the porous ceramicized alumina transition layer, and improve the balance of thermal conductivity, pressure resistance and interface reliability through the synergy of reactive polymer sealing layer and fully insulating ceramic thermally conductive filler network. Summary of the Invention
[0007] The purpose of this invention is to provide a high thermal conductivity and high pressure resistance ceramic aluminum substrate and its preparation method, so as to improve the technical problems of residual voids in the porous ceramic alumina transition layer, insufficient interfacial bonding stability between the aluminum substrate and the polymer insulating layer, and insufficient insulation stability of the thermally conductive filler system under high pressure resistance.
[0008] To achieve the above objectives, the present invention adopts the following technical solution: This invention provides a high thermal conductivity and high pressure resistance ceramic aluminum substrate, comprising an aluminum base layer, a porous ceramicized alumina transition layer, a reactive polymer sealing layer, a high thermal conductivity and high pressure resistance polymer insulating layer, and a copper foil layer stacked sequentially. The porous ceramicized alumina transition layer is disposed on at least one side surface of the aluminum base layer and has pores opening toward the high thermal conductivity and pressure resistant polymer insulating layer; The reactive polymer sealing layer includes an in-pore filling portion that fills the pores and a surface connection portion that covers the surface of the porous ceramicized alumina transition layer. The reactive polymer sealing layer is formed by curing a reactive interface component, which contains an alkoxysilane group, an epoxy group, and a third functional group. The third functional group is selected from at least one of an imide group, a phosphazene group, a borate ester group, and a borooxy heterocyclic group. The high thermal conductivity and pressure-resistant polymer insulating layer includes a cured resin matrix and an electrically insulating ceramic thermally conductive filler dispersed in the cured resin matrix.
[0009] Furthermore, the aluminum base layer is made of 1060 aluminum, 3003 aluminum alloy, 5052 aluminum alloy or 6061 aluminum alloy, and the thickness of the aluminum base layer is 0.5-3.0 mm. The porous ceramicized alumina transition layer is an anodic oxide layer, a hard anodic oxide layer, or a micro-arc oxide layer. Further, the filling depth of the pore-filling portion within the pores is 10%-90% of the thickness of the porous ceramicized alumina transition layer; the thickness of the surface connection portion is 0.2-10 μm.
[0010] Furthermore, the reactive interface component is selected from one or more of the following: epoxy silane-terminated imide oligomers, phosphazene-modified epoxy silane oligomers, borate ester-modified epoxy silane oligomers, and boron-oxyheterocyclic-modified epoxy silane oligomers. The reactive polymer sealing layer is formed by curing a sealing liquid. By weight, the sealing liquid includes 100 parts of reactive interface components, 5-60 parts of reactive diluent, 0.1-8 parts of curing aid, and 30-300 parts of organic solvent.
[0011] Furthermore, the cured resin matrix is formed by curing a resin composition, which, by weight, comprises 100 parts epoxy resin, 5-50 parts benzoxazine resin, 2-30 parts imide-modified epoxy resin or bismaleimide resin, 10-60 parts curing agent, and 0.05-5 parts curing accelerator.
[0012] Furthermore, the electrically insulating ceramic thermally conductive filler includes plate-shaped boron nitride, spherical aluminum nitride, and spherical alumina; Based on 100 parts by weight of the epoxy resin, the total amount of the electrically insulating ceramic thermally conductive filler is 120-300 parts by weight. The plate-shaped boron nitride has a D50 particle size of 3-30 μm and an aspect ratio of 10-200; the spherical aluminum nitride has a D50 particle size of 0.5-20 μm; and the spherical alumina has a D50 particle size of 0.05-10 μm.
[0013] Furthermore, at least a portion of the electrically insulating ceramic thermally conductive filler is treated with a surface treatment agent; Based on 100 parts by weight of the electrically insulating ceramic thermally conductive filler, the amount of the surface treatment agent is 0.2-5 parts by weight; The surface treatment agent is selected from one or more of aminosilane coupling agents, epoxysilane coupling agents, silane coupling agents containing phosphazene groups, silane coupling agents containing borate ester groups, and silane coupling agents containing imide groups. The high thermal conductivity and pressure resistant polymer insulating layer does not use graphene, carbon nanotubes, metal powders, transition metal chalcogenides or metal-organic framework materials as necessary thermally conductive fillers.
[0014] The present invention also provides a method for preparing the above-mentioned high thermal conductivity and high pressure resistance ceramic aluminum substrate, comprising the following steps: S1, perform surface pretreatment on the aluminum substrate; S2, ceramic treatment is performed on at least one side surface of the aluminum substrate to form a porous ceramic alumina transition layer with channels; S3, apply a sealing liquid containing reactive interface components to the porous ceramicized alumina transition layer and perform vacuum impregnation so that the sealing liquid at least partially enters the pores, and then perform pre-curing to form a reactive polymer sealing layer; S4, a thermally conductive and pressure-resistant insulating slurry containing a curing resin matrix precursor and an electrically insulating ceramic thermally conductive filler is coated onto the reactive polymer sealing layer, and then baked and semi-cured to form a high thermally conductive and pressure-resistant polymer insulating layer prefabricated layer. S5, copper foil is stacked on the high thermal conductivity and pressure resistant polymer insulating layer prefabrication layer, and vacuum hot pressing and post-curing are performed in sequence to obtain the high thermal conductivity and pressure resistant ceramic aluminum substrate; The reactive interface component contains an alkoxysilyl group, an epoxy group, and a third functional group, wherein the third functional group is selected from at least one of an imide group, a phosphazene group, a borate ester group, and a borooxy heterocyclic group. The electrically insulating ceramic thermally conductive filler includes at least two of boron nitride, aluminum nitride, and aluminum oxide.
[0015] Furthermore, in step S1, the surface pretreatment includes degreasing, alkaline washing, acid washing, water washing, and drying performed sequentially; The alkaline washing uses a sodium hydroxide solution with a mass fraction of 1%-10%, the treatment temperature is 30-70℃, and the treatment time is 0.5-5 min; The pickling process uses a nitric acid solution, sulfuric acid solution, or phosphoric acid solution with a mass fraction of 5%-30%, and the treatment time is 0.5-5 minutes. In step S2, the ceramicization treatment is either anodizing or micro-arc oxidation. When using anodizing, the voltage is 15-80V, the temperature is 5-30℃, and the treatment time is 10-90min. When using micro-arc oxidation, the voltage is 250-550V, the frequency is 200-1000Hz, and the processing time is 5-40min.
[0016] Further, in step S3, the sealing liquid is prepared according to the following steps: first, the reactive interface component, organic solvent and reactive diluent are mixed and stirred at 30-60℃ for 10-60 min, then the curing aid is added and stirring is continued for 5-30 min to obtain the sealing liquid; The vacuum impregnation process involves a vacuum degree of -0.08 to -0.10 MPa and an impregnation time of 2-20 min; the pre-curing temperature is 80-130℃ and the time is 5-30 min. In step S4, the thermally conductive and voltage-resistant insulating slurry is prepared according to the following feeding sequence: first, epoxy resin, benzoxazine resin, imide-modified epoxy resin or bismaleimide resin, curing agent and curing accelerator are mixed to obtain a resin mixture; then, electrically insulating ceramic thermally conductive filler is added to the resin mixture in batches and dispersed for 10-60 minutes to obtain the thermally conductive and voltage-resistant insulating slurry. The baking and semi-curing temperature is 80-140℃, and the time is 5-30 minutes; In step S5, the temperature of the vacuum hot pressing is 150-210℃, the pressure is 1.5-5MPa, and the time is 30-90min; the temperature of the post-curing is 180-230℃, and the time is 1-4h.
[0017] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. The porous ceramicized alumina transition layer of the present invention provides a ceramicized interface with channels. After vacuum impregnation, the reactive polymer sealing layer can form an in-pore filling portion, reducing residual voids in the channels and weak points at the interface, thereby improving breakdown stability and insulation retention after damp heat. The reactive polymer sealing layer also includes a surface connection portion covering the surface of the ceramicized alumina transition layer. This surface connection portion is continuously disposed with the in-pore filling portion, forming a continuous transition interface from the in-pore to the surface between the ceramicized layer and the high thermal conductivity and high voltage withstand polymer insulating layer, thereby improving copper foil peel strength and interlayer stability after thermal shock.
[0018] 2. The reactive interface component of this invention simultaneously comprises alkoxysilane groups, epoxy groups, and imide groups, phosphazene groups, borate ester groups, or borooxy heterocyclic groups. The alkoxysilane groups are used for anchoring the alumina pore walls, the epoxy groups are used for co-curing with the insulating resin, and the third functional group is used to improve the heat resistance, damp heat resistance, or electrical insulation stability of the interface layer. This makes the interface sealing layer not just a typical surface treatment layer, but a functional layer that combines pore sealing, interface reaction, and reliability enhancement. The high thermal conductivity and high voltage resistance polymer insulating layer uses at least two electrically insulating ceramic thermally conductive fillers selected from boron nitride, aluminum nitride, and alumina to construct a thermally conductive network, which can improve the continuity of the thermal conduction path while reducing the risk of electrical insulation fluctuations caused by conductive carbon materials or metal fillers.
[0019] 3. The present invention adopts the following sequence: first ceramicization, then reactive sealing, then coating of thermally conductive and pressure-resistant insulating slurry, and then hot pressing of copper lamination. This allows the pore sealing and interface connection to be pre-formed before the high-filler insulating slurry is applied, which helps to reduce the risk of failure caused by pressing gaps, filler agglomeration, and local lack of adhesive. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 This is a schematic diagram of a layered structure of a high thermal conductivity and pressure-resistant ceramic aluminum substrate according to the present invention.
[0022] Figure 2 This is a partially enlarged schematic diagram of the interface structure between the porous ceramicized alumina transition layer, the reactive polymer sealing layer, and the high thermal conductivity and pressure resistant polymer insulating layer of the present invention.
[0023] Figure 3 This is a schematic diagram of a process flow for the preparation method of a high thermal conductivity and pressure-resistant ceramic aluminum substrate according to the present invention.
[0024] Explanation of reference numerals in the attached figures: 1. Aluminum base layer; 2. Porous ceramicized alumina transition layer; 21. Channel; 3. Reactive polymer sealing layer; 31. In-pore filling part; 32. Surface connection part; 4. High thermal conductivity and pressure resistant polymer insulating layer; 41. Flake boron nitride; 42. Spherical aluminum nitride; 43. Spherical alumina; 5. Copper foil layer. Detailed Implementation
[0025] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0026] See Figure 1 As shown, the high thermal conductivity and pressure resistance ceramic aluminum substrate includes an aluminum base layer 1, a porous ceramicized alumina transition layer 2, a reactive polymer sealing layer 3, a high thermal conductivity and pressure resistance polymer insulating layer 4, and a copper foil layer 5. Figure 2 The pores 21 shown are located within the porous ceramicized alumina transition layer 2. The reactive polymer sealing layer 3 includes a pore filling portion 31 that enters the pores 21 and a surface connection portion 32 that covers the surface of the porous ceramicized alumina transition layer 2. The high thermal conductivity and pressure resistant polymer insulating layer 4 contains sheet-like boron nitride 41, spherical aluminum nitride 42 and spherical alumina 43. Figure 3 The preparation method shown includes, in sequence, aluminum substrate surface pretreatment, ceramicization treatment, vacuum impregnation and sealing, pre-curing, coating with thermally conductive and pressure-resistant insulating slurry, baking for semi-curing, laminating copper foil, vacuum hot pressing, and post-curing.
[0027] The following specific raw materials are used in the embodiments of this invention: the aluminum base layer is made of 1060-H24 industrial pure aluminum plate, 5052-H32 aluminum alloy plate, or 6061-T6 aluminum alloy plate; the copper foil is made of 35μm thick electrolytic copper foil; the epoxy resin is bisphenol A type epoxy resin E-51; the benzoxazine resin is bisphenol A-aniline type benzoxazine resin BA-a; the bismaleimide resin is 4,4′-diphenylmethane bismaleimide; the curing agent is phenolic resin curing agent; and the curing accelerator is... 2-Methylimidazole; the reactive diluent is 1,4-butanediol diglycidyl ether; the epoxy silane coupling agent is 3-glycidyl etheroxypropyltrimethoxysilane, i.e., KH-560; the aminosilane coupling agent is 3-aminopropyltriethoxysilane, i.e., KH-550; the solvent is butanone, cyclohexanone, or N,N-dimethylacetamide; the flake boron nitride is hexagonal boron nitride powder; the aluminum nitride is spherical aluminum nitride powder; the alumina is spherical α-Al2O3 powder and submicron α-Al2O3 powder.
[0028] In this embodiment of the invention, the epoxysilane-terminated imide oligomer is obtained by polyamic acid formation, end-group introduction, and imidization treatment of 4,4′-oxybisphthalic anhydride, 4,4′-diaminodiphenyl ether, 3-aminopropyltriethoxysilane, and 3-glycidoxypropyltrimethoxysilane in N,N-dimethylacetamide, resulting in an oligomer containing an imide structure, an alkoxysilyl group, and an epoxy group. The phosphazene-modified epoxysilane oligomer is formed by compounding or pre-reacting an epoxy resin containing a phosphazene structure with 3-glycidoxypropyltrimethoxysilane; the epoxy resin containing the phosphazene structure is hexa(4-glycidoxyphenoxy)cyclotriphosphazene. Boronate-modified epoxy silane oligomers can be obtained by esterification or compound pre-reaction of phenylboronic acid, neopentyl glycol diglycidyl ether and 3-glycidyl etheroxypropyltrimethoxysilane, so that the resulting oligomers contain boronate structure, alkoxysilyl group and epoxy group.
[0029] The electrically insulating ceramic thermally conductive filler can be surface-treated first. Specifically, flake boron nitride, spherical aluminum nitride, and alumina powder are added to a mixed solvent of ethanol and deionized water in a volume ratio of 95:5. The pH is adjusted to 4.5 with acetic acid, and KH-560 equivalent to 1.0% of the total filler mass is added. The mixture is stirred at 60°C for 2 hours, filtered, and dried at 110°C for 2 hours to obtain the surface-treated electrically insulating ceramic thermally conductive filler. This treatment is used to improve the interfacial compatibility between the ceramic filler and the epoxy resin system.
[0030] Example 1: The method for preparing a high thermal conductivity and pressure-resistant ceramic aluminum substrate in this embodiment includes the following steps: Step S1: Take a 1.5mm thick 5052-H32 aluminum alloy plate as the aluminum base layer. First, remove surface oil stains with an alkaline degreasing agent, then wash with a 5% sodium hydroxide aqueous solution at 50℃ for 2 minutes, followed by acid washing with a 15% nitric acid aqueous solution for 2 minutes, then rinse thoroughly with deionized water, and dry at 80℃ for 20 minutes to obtain the pretreated aluminum base layer.
[0031] Step S2: The pretreated aluminum substrate is placed in a 15% sulfuric acid aqueous solution for anodizing. The anodizing voltage is 45V, the electrolyte temperature is 20℃, and the treatment time is 45min. A porous ceramicized alumina transition layer with a thickness of approximately 30μm and a pore size of approximately 100-300nm is formed on one side of the aluminum substrate. After anodizing, it is washed with deionized water and dried at 80℃ for 20min.
[0032] Step S3: Preparation of sealing solution. 100 parts of epoxy silane-terminated imide oligomer, 30 parts of 1,4-butanediol diglycidyl ether, and 120 parts of butanone were added to a stirring container and stirred at 45°C for 30 min. Then, 1 part of 2-methylimidazole was added, and stirring continued for 15 min to obtain a sealing solution containing reactive interface components. The sealing solution was uniformly applied to the surface of the porous ceramicized alumina transition layer and impregnated under a vacuum of -0.09 MPa for 10 min to allow the sealing solution to enter the pores. Then, it was pre-cured at 105°C for 15 min to form a reactive polymer sealing layer with pore-filling and surface-connecting portions.
[0033] Step S4: Prepare a thermally conductive and voltage-resistant insulating slurry. Mix 100 parts of bisphenol A type epoxy resin E-51, 20 parts of bisphenol A-aniline type benzoxazine resin BA-a, 10 parts of 4,4′-diphenylmethane bismaleimide, 35 parts of phenolic resin curing agent, and 0.8 parts of 2-methylimidazole to obtain a resin mixture. Then, add 70 parts of flake-shaped hexagonal boron nitride, 80 parts of spherical aluminum nitride, 50 parts of spherical α-Al₂O₃, and 30 parts of submicron α-Al₂O₃ (all surface-treated with KH-560) to the resin mixture in batches and disperse for 30 minutes to obtain the thermally conductive and voltage-resistant insulating slurry. The sheet-like hexagonal boron nitride D50 particles have a diameter of approximately 10 μm and an aspect ratio of approximately 60; the spherical aluminum nitride D50 particles have a diameter of approximately 5 μm; the spherical α-Al₂O₃ D50 particles have a diameter of approximately 3 μm; and the submicron α-Al₂O₃ D50 particles have a diameter of approximately 0.3 μm. A thermally conductive and voltage-resistant insulating slurry is coated onto a reactive polymer sealing layer and baked at 110°C for 15 minutes to form a pre-fabricated high thermally conductive and voltage-resistant polymer insulating layer with a thickness of approximately 80 μm.
[0034] Step S5: An electrolytic copper foil with a thickness of 35 μm is stacked on a high thermal conductivity and pressure resistant polymer insulating layer prefabrication layer, vacuum hot-pressed at 180°C and 3 MPa for 60 min, and then post-cured at 210°C for 2 h to obtain the high thermal conductivity and pressure resistant ceramic aluminum substrate sample of Example 1.
[0035] Example 2: The method for preparing a high thermal conductivity and pressure-resistant ceramic aluminum substrate in this embodiment includes the following steps: Step S1: Take a 1.5mm thick 5052-H32 aluminum alloy plate as the aluminum base layer. First, degrease with an alkaline degreasing agent, then wash with a 5% sodium hydroxide aqueous solution at 50℃ for 2 minutes, followed by acid washing with a 15% nitric acid aqueous solution for 2 minutes. After thorough rinsing with deionized water, dry at 80℃ for 20 minutes to obtain the pretreated aluminum base layer.
[0036] Step S2: The pretreated aluminum substrate is placed in an aqueous micro-arc oxidation electrolyte containing 8 g / L sodium silicate, 3 g / L sodium hexametaphosphate, and 1 g / L potassium hydroxide for micro-arc oxidation treatment. The micro-arc oxidation voltage is 380 V, the frequency is 600 Hz, and the treatment time is 20 min. A porous ceramicized alumina transition layer with a thickness of approximately 40 μm and a pore size of approximately 0.3-1.5 μm is formed on one side of the aluminum substrate surface. After treatment, it is washed with deionized water and dried at 80 °C for 20 min.
[0037] Step S3: Preparation of sealing solution. 100 parts of phosphazene-modified epoxy silane oligomer, 35 parts of 1,4-butanediol diglycidyl ether, and 150 parts of cyclohexanone were added to a stirring container and stirred at 50°C for 40 min. Then, 2 parts of 2-methylimidazole were added, and stirring continued for 20 min to obtain the sealing solution. The sealing solution was applied to the surface of the porous ceramicized alumina transition layer and impregnated under a vacuum of -0.095 MPa for 15 min, followed by pre-curing at 115°C for 20 min to form a reactive polymer sealing layer.
[0038] Step S4: Prepare a thermally conductive and voltage-resistant insulating slurry. Mix 100 parts of bisphenol A type epoxy resin E-51, 30 parts of bisphenol A-aniline type benzoxazine resin BA-a, 15 parts of 4,4′-diphenylmethane bismaleimide, 45 parts of phenolic resin curing agent, and 1 part of 2-methylimidazole to obtain a resin mixture. Then, add 100 parts of flake-shaped hexagonal boron nitride, 120 parts of spherical aluminum nitride, 50 parts of spherical α-Al₂O₃, and 30 parts of submicron α-Al₂O₃ surface-treated with KH-560 in batches to the resin mixture and disperse for 45 minutes to obtain the thermally conductive and voltage-resistant insulating slurry. The sheet-like hexagonal boron nitride D50 has a particle size of approximately 15 μm and an aspect ratio of approximately 80; the spherical aluminum nitride D50 has a particle size of approximately 8 μm; the spherical α-Al₂O₃ D50 has a particle size of approximately 3 μm; and the submicron α-Al₂O₃ D50 has a particle size of approximately 0.3 μm. A thermally conductive and voltage-resistant insulating slurry is coated onto a reactive polymer sealing layer and baked at 120°C for 20 minutes to form a pre-fabricated high thermally conductive and voltage-resistant polymer insulating layer with a thickness of approximately 90 μm.
[0039] Step S5: An electrolytic copper foil with a thickness of 35 μm is stacked on a high thermal conductivity and pressure resistant polymer insulating layer prefabrication layer, vacuum hot-pressed at 190°C and 3.5 MPa for 70 min, and then post-cured at 220°C for 2 h to obtain the high thermal conductivity and pressure resistant ceramic aluminum substrate sample of Example 2.
[0040] Example 3: The method for preparing a high thermal conductivity and pressure-resistant ceramic aluminum substrate in this embodiment includes the following steps: Step S1: Take a 0.5mm thick 1060-H24 aluminum plate as the aluminum base layer. First, degrease it, then wash it with a 1% sodium hydroxide aqueous solution at 30℃ for 0.5min, followed by acid washing with a 5% nitric acid aqueous solution for 0.5min. After washing with deionized water, dry it at 70℃ for 20min to obtain the pretreated aluminum base layer.
[0041] Step S2: The pretreated aluminum substrate is placed in a 10% sulfuric acid aqueous solution for anodizing. The anodizing voltage is 15V, the electrolyte temperature is 20℃, and the treatment time is 10min. A porous ceramicized alumina transition layer with a thickness of about 5μm and a pore size of about 20-80nm is formed on one side of the aluminum substrate. After treatment, it is washed with deionized water and dried.
[0042] Step S3: Preparation of sealing solution. 100 parts of borate-modified epoxy silane oligomer, 5 parts of 1,4-butanediol diglycidyl ether, and 30 parts of butanone were added to a stirring container and stirred at 30°C for 10 min. Then, 0.1 parts of 2-methylimidazole were added, and stirring continued for 5 min to obtain the sealing solution. The sealing solution was applied to the surface of the porous ceramicized alumina transition layer and impregnated under a vacuum of -0.08 MPa for 2 min, followed by pre-curing at 80°C for 5 min to form a reactive polymer sealing layer.
[0043] Step S4: Prepare a thermally conductive and voltage-resistant insulating slurry. Mix 100 parts of bisphenol A type epoxy resin E-51, 5 parts of bisphenol A-aniline type benzoxazine resin BA-a, 2 parts of 4,4′-diphenylmethane bismaleimide, 10 parts of phenolic resin curing agent, and 0.05 parts of 2-methylimidazole to obtain a resin mixture. Then, add 30 parts of flake-shaped hexagonal boron nitride, 30 parts of spherical aluminum nitride, and 60 parts of spherical α-Al₂O₃ surface-treated with KH-560 in batches to the resin mixture and disperse for 10 minutes to obtain a thermally conductive and voltage-resistant insulating slurry. The flake-shaped hexagonal boron nitride D50 has a particle size of approximately 3 μm and an aspect ratio of approximately 20; the spherical aluminum nitride D50 has a particle size of approximately 0.8 μm; and the spherical α-Al₂O₃ D50 has a particle size of approximately 1 μm. Thermally conductive and pressure-resistant insulating slurry is coated onto a reactive polymer sealing layer and baked at 80°C for 5 minutes to form a pre-fabricated high thermally conductive and pressure-resistant polymer insulating layer with a thickness of approximately 30 μm.
[0044] Step S5: An electrolytic copper foil with a thickness of 35 μm is stacked on a high thermal conductivity and pressure-resistant polymer insulating layer prefabrication layer, vacuum hot-pressed at 150°C and 1.5 MPa for 30 min, and then post-cured at 180°C for 1 h to obtain the high thermal conductivity and pressure-resistant ceramic aluminum substrate sample of Example 3.
[0045] Example 4: The method for preparing a high thermal conductivity and pressure-resistant ceramic aluminum substrate in this embodiment includes the following steps: Step S1: Take a 3.0mm thick 6061-T6 aluminum alloy plate as the aluminum base layer. First, degrease it, then wash it with a 10% sodium hydroxide aqueous solution at 70℃ for 5 minutes, followed by acid washing with a 30% phosphoric acid aqueous solution for 5 minutes. After thorough rinsing with deionized water, dry it at 90℃ for 30 minutes to obtain the pretreated aluminum base layer.
[0046] Step S2: The pretreated aluminum substrate is placed in an aqueous micro-arc oxidation electrolyte containing 10 g / L sodium silicate, 5 g / L sodium hexametaphosphate, and 2 g / L potassium hydroxide for micro-arc oxidation treatment. The micro-arc oxidation voltage is 550 V, the frequency is 1000 Hz, and the treatment time is 40 min. A porous ceramicized alumina transition layer with a thickness of approximately 80 μm and a pore size of approximately 1-3 μm is formed on one side of the aluminum substrate surface. After treatment, it is washed with deionized water and dried.
[0047] Step S3: Preparation of sealing solution. 50 parts of epoxy silane-terminated imide oligomer, 50 parts of phosphazene-modified epoxy silane oligomer, 60 parts of 1,4-butanediol diglycidyl ether, and 300 parts of cyclohexanone were added to a stirring container and stirred at 60°C for 60 min. Then, 8 parts of 2-methylimidazole were added, and stirring continued for 30 min to obtain the sealing solution. The sealing solution was applied to the surface of the porous ceramicized alumina transition layer and impregnated under a vacuum of -0.10 MPa for 20 min, followed by pre-curing at 130°C for 30 min to form a reactive polymer sealing layer.
[0048] Step S4: Prepare a thermally conductive and voltage-resistant insulating slurry. Mix 100 parts of bisphenol A type epoxy resin E-51, 50 parts of bisphenol A-aniline type benzoxazine resin BA-a, 30 parts of 4,4′-diphenylmethane bismaleimide, 60 parts of phenolic resin curing agent, and 5 parts of 2-methylimidazole to obtain a resin mixture. Then, add 120 parts of flake-shaped hexagonal boron nitride, 120 parts of spherical aluminum nitride, 80 parts of spherical α-Al₂O₃, and 30 parts of submicron α-Al₂O₃ surface-treated with KH-560 in batches to the resin mixture and disperse for 60 minutes to obtain the thermally conductive and voltage-resistant insulating slurry. The sheet-like hexagonal boron nitride D50 has a particle size of approximately 30 μm and an aspect ratio of approximately 150; the spherical aluminum nitride D50 has a particle size of approximately 20 μm; the spherical α-Al₂O₃ D50 has a particle size of approximately 10 μm; and the submicron α-Al₂O₃ D50 has a particle size of approximately 0.5 μm. A thermally conductive and voltage-resistant insulating slurry is coated onto a reactive polymer sealing layer and baked at 140°C for 30 minutes to form a pre-fabricated high thermally conductive and voltage-resistant polymer insulating layer with a thickness of approximately 150 μm.
[0049] Step S5: An electrolytic copper foil with a thickness of 35 μm is stacked on a high thermal conductivity and pressure resistant polymer insulating layer prefabrication layer, vacuum hot-pressed at 210℃ and 5MPa for 90 min, and then post-cured at 230℃ for 4 h to obtain the high thermal conductivity and pressure resistant ceramic aluminum substrate sample of Example 4.
[0050] Comparative Example 1: The preparation method of the high thermal conductivity and pressure-resistant ceramic aluminum substrate in this comparative example includes the following steps: Step S1: A 1.5mm thick 5052-H32 aluminum alloy plate is used as the aluminum base layer. The plate is subjected to degreasing, alkaline washing, acid washing, water washing, and drying under the same conditions as in Example 1 to obtain the pretreated aluminum base layer.
[0051] Step S2: Anodizing is performed under the same conditions as in Example 1 to form a porous ceramicized alumina transition layer with a thickness of about 30 μm and a pore size of about 100-300 nm on one side of the aluminum substrate, followed by washing and drying.
[0052] In step S3, no sealing liquid is applied, and no vacuum impregnation or pre-curing treatment is performed, thus no reactive polymer sealing layer is formed.
[0053] Step S4: Prepare a thermally conductive and pressure-resistant insulating slurry in the same manner as in Example 1, and directly coat the slurry onto the porous ceramicized alumina transition layer. Bake at 110°C for 15 minutes to form a high thermally conductive and pressure-resistant polymer insulating pre-layer with a thickness of about 80 μm.
[0054] Step S5: Electrolytic copper foil with a thickness of 35 μm is stacked on a pre-fabricated high thermal conductivity and pressure resistant polymer insulating layer, vacuum hot-pressed at 180℃ and 3MPa for 60 min, and then post-cured at 210℃ for 2 h to obtain the sample of Comparative Example 1.
[0055] Comparative Example 2: The preparation method of the high thermal conductivity and pressure-resistant ceramic aluminum substrate in this comparative example includes the following steps: Step S1: Take a 1.5mm thick 5052-H32 aluminum alloy plate as the aluminum base layer. Perform degreasing, alkaline washing, acid washing, water washing, and drying under the same conditions as in Example 1.
[0056] Step S2: Anodizing is performed under the same conditions as in Example 1 to form a porous ceramicized alumina transition layer with a thickness of about 30 μm and a pore size of about 100-300 nm.
[0057] Step S3 involves applying a 1% (w / w) KH-560 ethanol / water solution to the surface of the porous ceramicized alumina transition layer, allowing it to stand for 10 minutes, and then drying it at 105°C for 15 minutes. This step only forms a standard silane treatment layer and does not form a reactive polymer sealing layer containing pore filling and surface bonding portions.
[0058] Step S4: Prepare a thermally conductive and voltage-resistant insulating slurry in the same manner as in Example 1, and coat the slurry onto the ceramicized alumina transition layer after ordinary silane treatment. Bake at 110°C for 15 minutes to form a high thermally conductive and voltage-resistant polymer insulating pre-layer with a thickness of about 80 μm.
[0059] Step S5: Electrolytic copper foil with a thickness of 35 μm is stacked on a pre-fabricated high thermal conductivity and pressure resistant polymer insulating layer, vacuum hot-pressed at 180℃ and 3MPa for 60 min, and then post-cured at 210℃ for 2 h to obtain the sample of Comparative Example 2.
[0060] Comparative Example 3: The preparation method of the high thermal conductivity and pressure-resistant ceramic aluminum substrate in this comparative example includes the following steps: Step S1: Take a 1.5mm thick 5052-H32 aluminum alloy plate as the aluminum base. The aluminum base is subjected to degreasing, mechanical roughening, pickling with a 15% nitric acid aqueous solution, water washing, and drying, but not anodizing, hard anodizing, or micro-arc oxidation.
[0061] In step S2, since no ceramic treatment is performed, a porous ceramic alumina transition layer is not formed on the surface of the aluminum substrate.
[0062] Step S3: Prepare the sealing liquid in the same manner as in Example 1, and apply the sealing liquid to the roughened aluminum substrate surface. Treat under a vacuum of -0.09 MPa for 10 min, and then pre-cur at 105°C for 15 min. Since there is no porous ceramicized alumina transition layer, this step cannot form an in-pore filling portion embedded in the ceramicized channels.
[0063] Step S4: Prepare a thermally conductive and pressure-resistant insulating slurry in the same manner as in Example 1, and coat the slurry onto the pre-cured surface layer. Bake at 110°C for 15 minutes to form a pre-fabricated high thermally conductive and pressure-resistant polymer insulating layer with a thickness of about 80 μm.
[0064] Step S5: Electrolytic copper foil with a thickness of 35 μm is stacked on a pre-fabricated high thermal conductivity and pressure resistant polymer insulating layer, vacuum hot-pressed at 180℃ and 3MPa for 60 min, and then post-cured at 210℃ for 2 h to obtain the comparative example 3 sample.
[0065] Comparative Example 4: The preparation method of the high thermal conductivity and pressure-resistant ceramic aluminum substrate in this comparative example includes the following steps: Step S1: Take a 1.5mm thick 5052-H32 aluminum alloy plate as the aluminum base layer. Perform degreasing, alkaline washing, acid washing, water washing, and drying under the same conditions as in Example 1.
[0066] Step S2: Anodizing is performed under the same conditions as in Example 1 to form a porous ceramicized alumina transition layer with a thickness of about 30 μm and a pore size of about 100-300 nm on one side of the aluminum substrate.
[0067] Step S3: Prepare and apply sealing liquid in the same manner as in Example 1, immerse in vacuum at -0.09 MPa for 10 min, and then pre-cur at 105°C for 15 min to form a reactive polymer sealing layer.
[0068] Step S4: Prepare a thermally conductive and voltage-resistant insulating slurry. Mix 100 parts of bisphenol A type epoxy resin E-51, 20 parts of bisphenol A-aniline type benzoxazine resin BA-a, 10 parts of 4,4′-diphenylmethane bismaleimide, 35 parts of phenolic resin curing agent, and 0.8 parts of 2-methylimidazole to obtain a resin mixture. Then, add 50 parts of flake-shaped hexagonal boron nitride, 20 parts of reduced graphene oxide powder, 80 parts of spherical aluminum nitride, 50 parts of spherical α-Al₂O₃, and 30 parts of submicron α-Al₂O₃ in batches to the resin mixture and disperse for 30 minutes to obtain a thermally conductive and voltage-resistant insulating slurry. Coat this slurry onto a reactive polymer sealing layer and bake at 110°C for 15 minutes to form a high thermally conductive and voltage-resistant polymer insulating pre-layer with a thickness of approximately 80 μm.
[0069] Step S5: Electrolytic copper foil with a thickness of 35 μm is stacked on a pre-fabricated high thermal conductivity and pressure resistant polymer insulating layer, vacuum hot-pressed at 180℃ and 3MPa for 60 min, and then post-cured at 210℃ for 2 h to obtain the comparative example 4 sample.
[0070] Comparative Example 5: The preparation method of the high thermal conductivity and pressure-resistant ceramic aluminum substrate in this comparative example includes the following steps: Step S1: Take a 0.5mm thick 1060-H24 aluminum plate as the aluminum base layer. Perform degreasing, alkaline washing, acid washing, water washing and drying in the same manner as in Example 3.
[0071] Step S2 involves subjecting the pretreated aluminum substrate to short-time anodizing to form an alumina layer with a thickness of approximately 3 μm, which is lower than the lower limit of the porous ceramicized alumina transition layer defined in this invention.
[0072] Step S3: Prepare the sealing liquid in a manner similar to that in Example 3, but shorten the vacuum impregnation time to 1 min, so that the target sealing depth is less than 10% of the thickness of the ceramicized alumina layer; then pre-cur at 80°C for 5 min.
[0073] Step S4: Prepare a thermally conductive and voltage-resistant insulating slurry. Mix 100 parts of bisphenol A type epoxy resin E-51, 5 parts of bisphenol A-aniline type benzoxazine resin BA-a, 2 parts of 4,4′-diphenylmethane bismaleimide, 10 parts of phenolic resin curing agent, and 0.05 parts of 2-methylimidazole to obtain a resin mixture. Then, add 25 parts of flake-shaped hexagonal boron nitride, 25 parts of spherical aluminum nitride, and 50 parts of spherical α-Al₂O₃ in batches to the resin mixture and disperse for 10 minutes to obtain a thermally conductive and voltage-resistant insulating slurry with a total filler content of 100 parts. Coat the slurry onto the pre-cured surface and bake at 80°C for 5 minutes to form an insulating pre-layer with a thickness of approximately 30 μm.
[0074] In step S5, an electrolytic copper foil with a thickness of 35 μm is stacked on the insulating pre-fabricated layer, vacuum hot-pressed at 150℃ and 1.5 MPa for 30 min, and then post-cured at 180℃ for 1 h to obtain the comparative example 5 sample.
[0075] Comparative Example 6: The preparation method of the high thermal conductivity and pressure-resistant ceramic aluminum substrate in this comparative example includes the following steps: Step S1: Take a 3.0mm thick 6061-T6 aluminum alloy plate as the aluminum base layer. Perform degreasing, alkaline washing, acid washing, water washing, and drying in the same manner as in Example 4.
[0076] Step S2: Perform micro-arc oxidation treatment under the same conditions as in Example 4 to form a porous ceramicized alumina transition layer with a thickness of about 80 μm and a pore size of about 1-3 μm.
[0077] Step S3: Prepare the sealing liquid in a manner similar to that in Example 4, and by increasing the single coating amount and extending the surface dwell time, make the surface interface thickness of the reactive polymer sealing layer approximately 15 μm, which is higher than the upper limit of the surface interface thickness specified in this invention. Then, immerse in the solution under a vacuum of -0.10 MPa for 20 min, and pre-cur at 130°C for 30 min.
[0078] Step S4: Prepare a thermally conductive and voltage-resistant insulating slurry. Mix 100 parts of bisphenol A type epoxy resin E-51, 50 parts of bisphenol A-aniline type benzoxazine resin BA-a, 30 parts of 4,4′-diphenylmethane bismaleimide, 60 parts of phenolic resin curing agent, and 5 parts of 2-methylimidazole to obtain a resin mixture. Then, add 140 parts of flake-shaped hexagonal boron nitride, 140 parts of spherical aluminum nitride, 90 parts of spherical α-Al₂O₃, and 30 parts of submicron α-Al₂O₃ in batches to the resin mixture and disperse for 60 minutes to obtain a thermally conductive and voltage-resistant insulating slurry with a total filler content of 400 parts. Coat this slurry onto a reactive polymer sealing layer and bake at 140°C for 30 minutes to form an insulating pre-layer with a thickness of approximately 150 μm.
[0079] In step S5, an electrolytic copper foil with a thickness of 35 μm is stacked on the insulating pre-fabricated layer, vacuum hot-pressed at 210℃ and 5MPa for 90 min, and then post-cured at 230℃ for 4 h to obtain the comparative example 6 sample.
[0080] Test items: Thermal conductivity testing was conducted using ASTM D5470-17(2024): the sample was cut into 25mm×25mm pieces, the test temperature was 25℃, and the contact pressure was 0.35MPa; before the test, the sample was placed at 23±2℃ and 50±5%RH for 24h, and the apparent thermal conductivity and thermal resistance were recorded.
[0081] The breakdown voltage test adopts IEC 60243-1:2013: the test uses 50Hz AC power, the voltage rise rate is 500V / s, the sample is placed in insulating oil to reduce the influence of edge discharge, and the breakdown voltage is divided by the insulation layer thickness to obtain the electrical strength.
[0082] The copper foil peel strength test was performed using IPC-TM-650 2.4.8.1: the copper foil was processed into a 3mm wide line, and a 90° peeling method was used with a peeling speed of 50mm / min.
[0083] Dielectric constant and dielectric loss were tested using IPC-TM-650 2.5.5.9: the test frequency was 1MHz, and the dielectric constant Dk and dielectric loss Df were recorded.
[0084] Volume resistivity was measured using an IPC-TM-650 2.5.17.1 with a test voltage of 500V DC. The reading was taken 60 seconds after the voltage was applied.
[0085] The solder thermal stress test was performed using IPC-TM-650 2.4.13.1: The sample was kept in a solder bath at 288±5℃ for 10 seconds, repeated 3 times, and the occurrence of blistering, bulging, copper foil delamination or interface delamination was observed.
[0086] The thermal shock test adopts IEC 60068-2-14:2023: the sample is subjected to temperature change cycles between -40℃ and 150℃, with each temperature held for 30 minutes, for a total of 300 cycles; after the cycles, the delamination is observed, and the copper foil peel strength is retested according to IPC-TM-6502.4.8.1, and the peel strength retention rate is calculated.
[0087] The damp heat test adopts IEC 60068-2-78:2012: the sample is placed in an environment of 85℃ and 85%RH for 168h. After treatment, the breakdown voltage is retested according to IEC 60243-1:2013, and the breakdown retention rate after damp heat is calculated.
[0088] The specific performance test results are shown in Tables 1 and 2 below: Table 1. Table 2. Analysis of experimental results: Compared with Comparative Example 1, Example 1 used the same 5052-H32 aluminum alloy plate, anodizing conditions, insulating slurry system, insulating layer thickness, copper foil, and hot pressing conditions. The difference was that Example 1 included a reactive polymer sealing layer, while Comparative Example 1 did not. Example 1 had a breakdown voltage of 7.08 kV, an electrical strength of 88.5 kV / mm, and a peel strength of 1.42 N / mm; Comparative Example 1 had a breakdown voltage of 5.24 kV, an electrical strength of 65.5 kV / mm, and a peel strength of 0.95 N / mm. After thermal shock, Example 1 had a peel retention rate of 89%, while Comparative Example 1 had a rate of 64%. After damp heat treatment, Example 1 had a breakdown retention rate of 85%, while Comparative Example 1 had a rate of 60%. These data demonstrate that the reactive polymer sealing layer can reduce the impact of pores and interface defects in the porous ceramicized alumina transition layer on breakdown and peel strength, thereby improving withstand voltage stability, interlayer bonding strength, and damp heat reliability.
[0089] Compared to Comparative Example 2, both Example 1 and Comparative Example 2 feature a porous ceramicized alumina transition layer. However, Example 1 uses a reactive interfacial component sealing layer containing alkoxysilane groups, epoxy groups, and imide groups, while Comparative Example 2 only uses KH-560 ordinary silane treatment. The breakdown voltage of Comparative Example 2 is 5.84 kV, and the peel strength is 1.12 N / mm, showing improvement over Comparative Example 1, but still weaker than Example 1's 7.08 kV and 1.42 N / mm. This result indicates that ordinary small-molecule silane treatment can improve interfacial wetting and coupling to some extent, but it is difficult to form a continuous reactive polymer sealing layer with pore-filling and surface-connecting portions. The multifunctional reactive interfacial component of this invention can not only bond with the alumina pore walls but also co-cur and bond with the subsequent resin layer through epoxy groups.
[0090] Compared to Comparative Example 3, Example 1 has a porous ceramicized alumina transition layer, while Comparative Example 3 only involves degreasing, roughening, and pickling of the aluminum substrate, without forming a ceramicized pore structure. The thermal conductivity of Comparative Example 3 is 4.48 W / (m·K), which is close to that of Example 1 (4.61 W / (m·K). However, the breakdown voltage of Comparative Example 3 is only 4.74 kV, the peel strength is only 0.83 N / mm, and the peel retention rate after thermal shock is only 56%, all significantly lower than that of Example 1. This trend indicates that the porous ceramicized alumina transition layer not only provides a general oxide interface but also provides anchoring points within the pores and an insulating transition structure, enabling the reactive sealing layer to form a stable pore-filling portion and surface connection portion.
[0091] Compared to Comparative Example 4, Example 1 also features a porous ceramicized alumina transition layer and a reactive polymer sealing layer. The difference lies in Comparative Example 4, which uses reduced graphene oxide powder to replace part of the sheet-like boron nitride. The thermal conductivity of Comparative Example 4 is 5.37 W / (m·K), higher than that of Example 1 (4.61 W / (m·K), indicating that graphene-like materials contribute to improving thermal conductivity. However, Comparative Example 4 exhibits a breakdown voltage of 4.18 kV, an electrical strength of 52.2 kV / mm, a dielectric loss Df of 0.041, and a volume resistivity of 5.8 × 10⁻⁶. 12 The Ω·cm values were significantly weaker than those in Example 1. This trend indicates that in high thermal conductivity and high voltage resistance ceramic aluminum substrates, simply improving thermal conductivity does not equate to improved overall performance; a fully insulating ceramic thermally conductive filler network composed of boron nitride, aluminum nitride, and alumina is more conducive to balancing thermal conductivity and electrical insulation stability.
[0092] Compared to Comparative Example 5, Example 3 falls within the lower boundary of this invention, while Comparative Example 5 reduces the thickness of the ceramicized alumina layer, the sealing depth, and the total filler amount to below the limits set by this invention. Example 3 exhibits a thermal conductivity of 3.02 W / (m·K), a breakdown voltage of 2.30 kV, and a peel strength of 1.06 N / mm; the corresponding values for Comparative Example 5 are 2.77 W / (m·K), 1.48 kV, and 0.86 N / mm, respectively. This trend indicates that when the thickness of the ceramicized alumina transition layer is insufficient, the sealing depth is insufficient, and the total filler amount is low, pore sealing, thermal conductivity path construction, and interfacial bonding are all affected. Therefore, the lower limits set by this invention regarding the ceramicized layer thickness, sealing depth, and total filler amount are reasonable.
[0093] Compared to Comparative Example 6, Example 4 is located at the high-end boundary of the present invention, while Comparative Example 6 further increases the total filler volume and makes the surface connection thickness exceed the range defined by the present invention. Example 4 has a thermal conductivity of 4.83 W / (m·K) and a thermal resistance of 0.34 K·cm. 2 The peel strength was 1.27 N / mm; the thermal conductivity of Comparative Example 6 was 4.62 W / (m·K), and the thermal resistance was 0.40 K·cm. 2 / W, with a peel strength of 0.73 N / mm. Although Comparative Example 6 used a higher filler content, the thermal conductivity did not improve further; instead, the peel strength decreased and the thermal resistance increased. This trend indicates that excessive filler may lead to increased slurry viscosity, decreased compression fluidity, filler agglomeration, and increased interfacial stress; excessively thick surface joints may also increase interfacial thermal resistance and interlayer stress. Therefore, the upper limits set by this invention regarding the total filler content and the thickness of the surface joint are reasonable.
[0094] A comparison between Examples 1, 2, 3, and 4 further illustrates that Example 2, as a preferred embodiment, has a thermal conductivity of 5.25 W / (m·K) and a thermal resistance of 0.24 K·cm. 2 / W, with a breakdown voltage of 8.30kV, a peel strength of 1.55N / mm, a peel retention rate of 92% after thermal shock, and a breakdown retention rate of 88% after damp heat, showing better overall performance than the central and boundary embodiments. Embodiment 4, due to its thicker insulation layer, achieves an absolute breakdown voltage of 10.14kV, but its thermal resistance, peel strength, and reliability are inferior to Embodiment 2.
[0095] In summary, reactive polymer sealing layers improve breakdown voltage, post-hygrothermal breakdown retention, and peel strength; porous ceramicized alumina transition layers improve interface anchoring, pressure resistance, and thermal shock stability; fully insulating ceramic thermally conductive filler networks balance thermal conductivity and electrical insulation stability; and the upper and lower limits of parameter ranges provide a reasonable balance between processability, thermal resistance, and reliability.
[0096] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
[0097] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A high thermal conductivity and pressure-resistant ceramic aluminum substrate, characterized in that, It includes an aluminum base layer, a porous ceramicized alumina transition layer, a reactive polymer sealing layer, a high thermal conductivity and pressure resistant polymer insulating layer, and a copper foil layer, which are stacked in sequence. The porous ceramicized alumina transition layer is disposed on at least one side surface of the aluminum base layer and has pores opening toward the high thermal conductivity and pressure resistant polymer insulating layer; The reactive polymer sealing layer includes an in-pore filling portion filling the pores and a surface connection portion covering the surface of the porous ceramicized alumina transition layer; the filling depth of the in-pore filling portion in the pores is 10%-90% of the thickness of the porous ceramicized alumina transition layer; the thickness of the surface connection portion is 0.2-10 μm; The reactive polymer sealing layer is formed by curing a reactive interface component, which contains an alkoxysilane group, an epoxy group, and a third functional group. The third functional group is selected from at least one of an imide group, a phosphazene group, a borate ester group, and a borooxy heterocyclic group. The high thermal conductivity and pressure-resistant polymer insulating layer includes a cured resin matrix and an electrically insulating ceramic thermally conductive filler dispersed in the cured resin matrix; the cured resin matrix is formed by curing a resin composition, which, by weight, includes 100 parts epoxy resin, 5-50 parts benzoxazine resin, 2-30 parts imide-modified epoxy resin or bismaleimide resin, 10-60 parts curing agent, and 0.05-5 parts curing accelerator.
2. The high thermal conductivity and pressure-resistant ceramic aluminum substrate according to claim 1, characterized in that, The aluminum base layer is made of 1060 aluminum, 3003 aluminum alloy, 5052 aluminum alloy or 6061 aluminum alloy, and the thickness of the aluminum base layer is 0.5-3.0 mm.
3. The high thermal conductivity and pressure-resistant ceramic aluminum substrate according to claim 1, characterized in that, The reactive interface component is selected from one or more of the following: epoxy silane-terminated imide oligomers, phosphazene-modified epoxy silane oligomers, borate ester-modified epoxy silane oligomers, and boron-oxygen heterocyclic-modified epoxy silane oligomers. The reactive polymer sealing layer is formed by curing a sealing liquid. By weight, the sealing liquid includes 100 parts of reactive interface components, 5-60 parts of reactive diluent, 0.1-8 parts of curing aid, and 30-300 parts of organic solvent.
4. The high thermal conductivity and pressure-resistant ceramic aluminum substrate according to claim 1, characterized in that, The electrically insulating ceramic thermally conductive filler includes plate-shaped boron nitride, spherical aluminum nitride, and spherical alumina; based on 100 parts by weight of the epoxy resin, the total amount of the electrically insulating ceramic thermally conductive filler is 120-300 parts by weight.
5. The high thermal conductivity and pressure-resistant ceramic aluminum substrate according to claim 1, characterized in that, At least a portion of the electrically insulating ceramic thermally conductive filler is treated with a surface treatment agent; the amount of the surface treatment agent is 0.2-5 parts by weight per 100 parts by weight of the electrically insulating ceramic thermally conductive filler.
6. A method for preparing a high thermal conductivity and high pressure resistance ceramic aluminum substrate, characterized in that, Includes the following steps: S1, perform surface pretreatment on the aluminum substrate; S2, ceramic treatment is performed on at least one side surface of the aluminum substrate to form a porous ceramic alumina transition layer with channels; S3, apply a sealing liquid containing reactive interface components to the porous ceramicized alumina transition layer and perform vacuum impregnation so that the sealing liquid at least partially enters the pores, and then perform pre-curing to form a reactive polymer sealing layer; S4, a thermally conductive and pressure-resistant insulating slurry containing a curing resin matrix precursor and an electrically insulating ceramic thermally conductive filler is coated onto the reactive polymer sealing layer, and then baked and semi-cured to form a high thermally conductive and pressure-resistant polymer insulating layer prefabricated layer. S5, copper foil is stacked on the high thermal conductivity and pressure resistant polymer insulating layer prefabrication layer, and vacuum hot pressing and post-curing are performed in sequence to obtain the high thermal conductivity and pressure resistant ceramic aluminum substrate.
7. The method for preparing a high thermal conductivity and pressure-resistant ceramic aluminum substrate according to claim 6, characterized in that, In step S2, the ceramicization treatment is either anodizing or micro-arc oxidation. When using anodizing, the voltage is 15-80V, the temperature is 5-30℃, and the treatment time is 10-90min; When using micro-arc oxidation, the voltage is 250-550V, the frequency is 200-1000Hz, and the processing time is 5-40min. In step S3, the sealing liquid is prepared according to the following steps: first, the reactive interface component, organic solvent and reactive diluent are mixed and stirred at 30-60℃ for 10-60 min, then the curing aid is added and stirring is continued for 5-30 min to obtain the sealing liquid; The vacuum degree of the vacuum impregnation is -0.08 to -0.10 MPa, and the impregnation time is 2-20 min; the pre-curing temperature is 80-130℃, and the time is 5-30 min.
8. The method for preparing a high thermal conductivity and pressure-resistant ceramic aluminum substrate according to claim 6, characterized in that, In step S4, the thermally conductive and pressure-resistant insulating slurry is prepared according to the following steps: first, epoxy resin, benzoxazine resin, imide-modified epoxy resin or bismaleimide resin, curing agent and curing accelerator are mixed to obtain a resin mixture; then, electrically insulating ceramic thermally conductive filler is added to the resin mixture in batches and dispersed for 10-60 minutes to obtain the thermally conductive and pressure-resistant insulating slurry. The baking and semi-curing temperature is 80-140℃, and the time is 5-30 minutes; In step S5, the temperature of the vacuum hot pressing is 150-210℃, the pressure is 1.5-5MPa, and the time is 30-90min; the temperature of the post-curing is 180-230℃, and the time is 1-4h.